(3GdCef GdLeGYj hGdJWhQGJ GdOhdjI GdeYGUQI (B/ s - (3eMeO Hf GdUOjb HZI s; (3GTQa YQaGJ SdjeGf CHhMLGRI s; (3YGFTI QGJHs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3djS ef GdeHGdZI Gdbhd HCf eGTgOg GdYGde ef JWhQGJ HYO CMOGK (B11 (3SHJeHQ (B2001 (3bO COi Edi GfgjGQ fXGe GdCee GdeJMOI ddCef GdLeGYi abO cGf ef fJGFL GdMQH Ydi GdEQgGH hZRh GdYQGb Cf MOK GfJgGc SGaQ ddeHGOiA GdJj bGe YdjgG fXGe GdCef GdLeGYi NGUI MXQ GSJNOGe GdbhI Ch GdJgOjO HgG aj GdYdGbGJ GdOhdjI hGdGdJRGe HMd GdfRGYGJ GdOhdjI HGdWQb GdSdejI hYOe GdJONd aj GdTDhf GdOGNdjI ddOhd ceG LQi JLGhR dSdWGJ GdCee GdeJMOI hNGUI eLdS GdCef GdOhdj aj MaX GdSde hGdCef GdOhdjjf hehGLgI GdYOhGfs
(3GWQhMI (B( (3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B468-509s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdCef GdLeGYj s; (3GdJWhQGJ GdOhdjI GdeYGUQI s; (3efY GSJNOGe GdbhI aj GdYdGbGJ GdOhdjIs; (3eLdS GdGef GdOhdj hGdGef GdLeGYj s; (3GdfXGe GdGbdjej ddCef GdLeGYj s; (3GdGef GdLeGYj hGdMQH Ydj GdYQGb s; (3GdMQH GdGSQGFjdjI Ydj YRI s; (3eSJbHd GdGef GdLeGYj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs